CONFLICTS AMONG STUDENTS FROM 8 TO 9 YEARS OLD: TEASING AND ANNOYING BEHAVIOR - Ferreira da Silva, Livia Maria [UNESP]; Vinha, Telma Pileggi [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
Based on the Piagetian perspective, this qualitative and quantitative study sought to investigate the causes of conflicts among primary school students. Thirty children aged 8 and 9 from a primary school, selected according to the criterion of convenience. Data were collected through 23 sessions of observation of the interactions between the children in different moments of the school routine until the saturation of the data, criterion chosen to leave the field. In some situations, it was necessary to have an informal conversation with the participants to better understand the conflict. The results indicated that the main cause of conflict among students was teasing, annoying behavior and physical dispute. It discusses the influence of cognitive, affective and moral development, as well as the cultural aspects that influence the experience of the conflict. It is recommended the implementation of educational interventions that, in addition to approaching conflicts with students, invest in strategies for valuing ethical coexistence.
Keywords: Interpersonal conflicts; Constructivism: education; Causes